ICAM-1 on Breast Cancer Cells Suppresses Lung Metastasis but Is Dispensable for Tumor Growth and Killing by Cytotoxic T Cells - Regev, Ofer; Kizner, Marina; Roncato, Francesco; Dadiani, Maya; Saini, Massimo; Castro-Giner, Francesc; Yajuk, Olga; Kozlovski, Stav; Levi, Nehora; Addadi, Yoseph; Golani, Ofra; Ben-Dor, Shifra; et al. (Frontiers in Immunology, 2022)
Breast tumors and their derived circulating cancer cells express the leukocyte β2 integrin ligand Intercellular adhesion molecule 1 (ICAM-1). We found that elevated ICAM-1 expression in breast cancer cells results in a favorable outcome and prolonged survival of breast cancer patients. We therefore assessed the direct in vivo contribution of ICAM-1 expressed by breast cancer cells to breast tumorigenesis and lung metastasis in syngeneic immunocompetent mice hosts using spontaneous and experimental models of the lung metastasis of the C57BL/6-derived E0771 cell line, a luminal B breast cancer subtype. Notably, the presence of ICAM-1 on E0771 did not alter tumor growth or the leukocyte composition in the tumor microenvironment. Interestingly, the elimination of Tregs led to the rapid killing of primary tumor cells independently of tumor ICAM-1 expression. The in vivo elimination of a primary E0771 tumor expressing the ovalbumin (OVA) model neoantigen by the OVA-specific OVA-tcr-I mice (OT-I) transgenic cytotoxic T lymphocytes (CTLs) also took place normally in the absence of ICAM-1 expression by E0771 breast cancer target cells. The whole lung imaging of these cells by light sheet microscopy (LSM) revealed that both Wild type (WT)- and ICAM-1-deficient E0771 cells were equally disseminated from resected tumors and accumulated inside the lung vasculature at similar magnitudes. ICAM-1-deficient breast cancer cells developed, however, much larger metastatic lesions than their control counterparts. Strikingly, the vast majority of these cells gave rise to intravascular tumor colonies both in spontaneous and experimental metastasis models. In the latter model, ICAM-1 expressing E0771- but not their ICAM-1-deficient counterparts were highly susceptible to elimination by neutrophils adoptively transferred from E0771 tumor-bearing donor mice. Ex vivo, neutrophils derived from tumor-bearing mice also killed cultured E0771 cells via ICAM-1-dependent interactions. Collectively, our results are a first indication that ICAM-1 expressed by metastatic breast cancer cells that expand inside the lung vasculature is involved in innate rather than in adaptive cancer cell killing. This is also a first indication that the breast tumor expression of ICAM-1 is not required for CTL-mediated killing but can function as a suppressor of intravascular breast cancer metastasis to lungs.